Optimized design of sensing transmission and computing collaborative industrial Internet - Jingbo LI; Li MA; Yang LI; Yingxun FU; Dongchao MA (Tongxin xuebao)
In view of the new scenario and time-sensitive requirements of sensing-transmission end to computing end in the industrial Internet, and to solve the problem of end-to-end delay in applications that were not up to standard, a network optimized design scheme for sensing-transmission cooperative computing was proposed.First, the sensing-transmission computing cooperative network architecture based on cloud-edge-end was proposed to promote the deep integration of multidimensional systems and heterogeneous resources.Secondly, the network topology construction mode was optimized to reduce the average path length of the network, shorten the propagation distance, and offset the problem of signal decay due to the use of higher frequencies.Finally, the routing method was improved, and an integrated algorithm of topology optimization and routing strategy was designed to reduce the queuing delay in the network, control the end-to-end delay within a bounded range, and weaken the “long tail phenomenon”.The experimental results show that the scheme reduces the end-to-end delay and ensures the real-time and reliability of the network by optimizing the network topology and routing strategy and integrating the design.